Pengaruh Penerapan Metode Show and Tell Terhadap Pembelajaran Tematik pada Keterampilan Berbicara Siswa SDN 2 Ciloa Kabupaten Kuningan - Aisyah, Nelvin Kania Nur; Usamah, Asep (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to determine the effect of the application of the Show And Tell Method on thematic learning on the speaking skills of students of SDN 2 Ciloa, Kuningan Regency. This research method is a pre-experimental quantitative with a one-group posttest pretest design. The research was carried out in grade III of SDN 2 Ciloa, Kuningan Regency. The researcher took a sample of class III as many as 30 students. The instrument to obtain data on the speaking skills of grade III elementary school students uses observation sheets and assessment rubrics. The data collection techniques in this study are in the form of observation, rubrics, and documentation. Data processing and data analysis and testing the hypothesis using SPSS Version 25, if the data is declared normal and homogeneous, the t-Test Technique will be used, if the data is abnormal or homogeneous, a non-parametric test will be carried out. The results of the data analysis showed that the use of the show and tell learning method had an effect on speaking skills, so that it could improve the speaking skills of grade III students of SDN 02 Ciloa, Kuningan Regency